Taguchi-Based Optimization Technique in Reflux Microwave Extraction of Piperine from Black Pepper (Black Pepper (Piper nigrum) - Nour, A. H.; Olalere, Olusegun Abayomi (AENSI Publishing, 2016)
In recent times, major concern had been placed on the medicinal and clinical use of Piperine; amajor component of black pepper. The need then arises to qualitatively extract Piperine using an extraction method with a minimal sample usage, shorter irradiation time, lower solvent consumption, reduced solvent contamination and a higher extraction yield, among other factors. Microwave reflux extraction is such method which united the microwave and traditional solvent extraction with the merit of shorter extraction time, low solvent consumption and higher extraction rate. A Taguchi-based orthogonal optimization design was therefore employed using Minitab 17® to investigate the combined effects of four numerical factors on the extraction of Piperine from black pepper under the reflux microwave extraction method. From the results obtained, the optimum conditions revealed that irradiation time, microwave power level, feed particle size, and solvent-to-feed ratio has an optimum value of 90mins,350W,0.105mm, and 10mL/g respectively ranked in concordant to their extremum(Delta) differences. At this point the optimum conditions were validated to have a Piperine yield of 2.058% w/w. Moreover, the Relative Standard deviations of 0.62% and 0.30% from the confirmatory and spectrometric repeatability respectively indicated a better prediction of a good precision for the robust parametric Taguchi experimental designs. Hence, the optimized setting from this study offered a pragmatic approach in the industrial scaling up of Piperine from black pepper via reflux microwave method.